Improving open information extraction using domain knowledge - Emani, C.K.; Ferreira da Silva, C.; Fiès, B.; Ghodous, P. (Proc. of Surfacing the Deep and the Social Web (SDSW), co-located with the 13th International Semantic Web Conference (ISWC 2014), 2014)
Open Information Extraction (OIE) aims to identify all the possible assertions within a sentence. Recent and thus the most efficient OIE-tools use the grammatical dependencies or the syntactic tree of the sentence to perform extraction. When they provide a wrong extraction it is mainly due to parsing errors. In this paper, we propose to handle these parsing errors before doing OIE itself. To achieve our goal we focus on multi-word expressions (MWE). They represent more than 45% of wrong extractions. We show how the MWE-problem can be handle in a given domain and how MWE-unbreakable property is a good filter for OIE.